Fundamentos para uma ética do horizonte: o jornalismo construtivo como elo entre cidadania e futuro - Pereira, Guilherme Lucian (2022)
This thesis proposes to investigate a variation of journalistic discourse that acts in the composition of constructive enunciation, and its purpose is to reassemble, as far as possible, the scripts of History that authorized for journalism a particular type of knowledge based on semantic chains and in the logical con-nections necessary for the formation of a repertoire of transformative evocations. The speculations that will be presented are articulated with emerging public values, and serve both to understand the discursive phenomena investigated and the search for a communicational centrality that gives epistemological cohe-sion to the symbolic arrangement of the evocations of this configuration of journalism. The approach we adopt is that of Foucault’s archeology — insofar as the statements of a constructive journalistic activity are associated with the socio-historical positions occupied by the plots of its discourse, considering the fundamental values for reviewing your responsibility and your system of ideas. It is, therefore, about de-fining the sayable limits of an enunciative extension common to the ethical exercise of the profession, which is capable of reflecting in the daily life the project of words that are oriented to the protection of life. Foucault’s discourse theory allowed us to associate the normative character of the Horizon Ethics and the pronunciations that are oriented towards the conservation of human destiny; and the tendency of our deconstruction of words and meanings points to the consolidation of an emancipatory repertoire. As for the empirical anchoring, the linguistic-symbolic aspects of the content of 3258 textual segments from the articles published by the “Muda Tudo”, Positive News and Reset websites were observed, which gave rise to twelve thematic classes that are correlated to constructive enunciation. The results of this work, after all, can make clear the open possibilities of pronunciations that condition journalism to change collective attitudes towards the future.